Simulation of a photovoltaic panels by using Matlab/Simulink - Bilhan, Ayse Kocalmis; Caliskan, Abuzer; Unal, Sencer (Institute of Electrical and Electronics Engineers Inc., 2017)
In recent years, it is getting attention for renewable energy sources such as solar energy, fuel cells, batteries or ultracapacitors for distributed power generation systems. This paper proposes a general mathematical model of solar cells and Matlab/Simulink software based simulation of this model has been visually programmed. Proposed model can be used with other hybrid systems to develop solar cell simulations. Also, all equations are performed by using Matlab/Simulink programming. © 2016 IEEE.
8th International Conference on Electronics, Computers and Artificial Intelligence, ECAI 2016 -- 30 June 2016 through 2 July 2016 -- Ploiesti -- 126585
Keywords: Generalized model; PV cell; PV modeling